(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the results of outpatient management activities for patients with type 2 diabetes at Tieu Can District Regional General Hospital, Tra Vinh Province, during 2023–2024. Methods: Medical records of type 2 diabetes patients were reviewed, supplemented by in-depth interviews with healthcare staff and patients. Collected data focused on five key areas: (1) screening/diagnosis, (2) creation of medical records and treatment monitoring books, (3) development and follow-up of treatment plans, (4) routine re-examinations, and (5) health communication/counseling. Results: From April 2023 to April 2024, 181 newly diagnosed type 2 diabetes patients were enrolled in outpatient management. Monthly blood glucose testing, quarterly HbA1c and lipid profiles were conducted in 92.8%, 53.0%, and 86.7% of cases, respectively. About 84.5% of patients attended scheduled re-examinations. However, counseling sessions were limited in both content and duration. Treatment goals were met in 70.2% of patients for fasting blood glucose (<7.2 mmol/L) and in 74.0% for HbA1c (<7%). Conclusion: Core outpatient management activities for type 2 diabetes were implemented, though gaps remain in screening, counseling, and health communication. Continued efforts are needed to enhance screening, counseling, appointment reminders, and routine testing to improve treatment monitoring.